Coefficient Bounds for a Certain Family of Biunivalent Functions Defined by Gegenbauer Polynomials - Isra Al-Shbeil; Abbas Kareem Wanas; Abdelkader Benali; Adriana Cătaş (Journal of Mathematics)
In the present work, by making use of Gegenbauer polynomials, we introduce and study a certain family of λ-pseudo bistarlike and λ-pseudo biconvex functions with respect to symmetrical points defined in the open unit disk. We obtain estimates for initial coefficients and solve the Fekete–Szego¨ problem for functions that belong to this family. Furthermore, we give connections to some of the earlier known results.